2012
DOI: 10.1509/jppm.08.043
|View full text |Cite
|
Sign up to set email alerts
|

A Coconstructed World: Adolescent Self-Socialization on the Internet

Abstract: This article examines the ubiquitous Internet as a context for socialization for both younger and older adolescents. This research finds that the Internet adds dimensions to and takes away elements in the socialization process that have not been manifest in the same way in the past. The Internet serves as both an influence agent and an interactive context in which socialization and identity development takes place. The authors find that the lack of the usual adult socialization agents in this context challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…For example, a number of authors (Clarke, Goodchild and Harrison, 2010;Willett, 2009;Boyd, 2007) have variously identified that young people (ranging in age from eight to 18 years) engage in SNS behaviours such as profile decoration and game-playing for the purposes of entertainment and the alleviation of boredom. The literature has also acknowledged that a key motivation is that of identity management (Anderson and McCabe, 2012;Stern, 2008;Willett, 2008). For example, Livingstone and Brake (2010) observe that teenagers' use of SNS is motivated by a wish to present a positive identity that wins the social validation of one's peers.…”
Section: Commercial Presence On Social Networking Sitesmentioning
confidence: 99%
“…For example, a number of authors (Clarke, Goodchild and Harrison, 2010;Willett, 2009;Boyd, 2007) have variously identified that young people (ranging in age from eight to 18 years) engage in SNS behaviours such as profile decoration and game-playing for the purposes of entertainment and the alleviation of boredom. The literature has also acknowledged that a key motivation is that of identity management (Anderson and McCabe, 2012;Stern, 2008;Willett, 2008). For example, Livingstone and Brake (2010) observe that teenagers' use of SNS is motivated by a wish to present a positive identity that wins the social validation of one's peers.…”
Section: Commercial Presence On Social Networking Sitesmentioning
confidence: 99%
“…Socialization in general refers to the introduction of children into an existing social group, enabling them to adopt approved behaviors and values [14]. If we consider environmental values, the social group into which adolescents are socialized may not actually be competent in this field-adolescents for many reasons (school, media, peers, Internet) may be more knowledgeable than their parents [4].…”
Section: The Impact Of Culture On Ecological Resocializationmentioning
confidence: 99%
“…"processes by which young people acquire skills, knowledge, and attitudes relevant to their functioning as consumers in the marketplace" (Ward, 1980, p. 382). And while many potential agents, such as friends, other adults, or organizations, also participate in the socialization of children (Moschis & Churchill, 1978), including adaptation to the marketplace, parents are the primary socialization agents of children (Anderson & McCabe, 2012).…”
mentioning
confidence: 99%